Hip rotation as a risk factor of anterior cruciate ligament injury in female athletes - Yasuda, T.; Yokoi, Y.; Oyanagi, K.; Hamamoto, K. (The Journal of Physical Fitness and Sports Medicine, 2016)
No specific hip joint anatomy has been identified as a risk factor for anterior cruciate ligament (ACL) injury in females. This study was conducted to elucidate the correlation of hip rotation with ACL injury incidence in female handball players, and to clarify the association of hip rotation with knee valgus motion, during ACL injury screening tasks, that is a strong predictor of ACL injury. Of 17 female university handball players, the 8 ACL-injured players displayed greater internal and smaller external rotation of the hip than the 9 uninjured players. Logistic regression analyses demonstrated significant association between hip rotation and ACL injury. Hip internal rotation dominance (internal rotation range is greater than external one) was found in 7 out of the 8 ACL-injured females in contrast to 3 out of the 9 uninjured. Knee valgus was induced in 24 and 22 of the 31 healthy female volunteers by vertical jump and single-leg squat tests, respectively. The knee valgus-positive females showed a smaller range of hip external rotation than the negative ones, which was significantly associated with knee valgus during the screening tests. Hip internal rotation dominance was significantly related to knee valgus induced by each screening test. In contrast to the females, male subjects showed lower rates of knee valgus induction by the screening tests, whereas there was no clear association between hip internal rotation dominance and the knee valgus induction. The present findings may indicate the important role of hip rotation measurement in identification of females at risk for ACL injury.